Quantitative assessment of ventilation-perfusion relationships with gallium-68 positron emission tomography/computed tomography imaging in lung cancer patients. (April 2022) - Li, Zhuorui; Le Roux, Pierre-Yves; Callahan, Jason; Hardcastle, Nicholas; Hofman, Michael S.; Siva, Shankar; Yamamoto, Tokihiro
Highlights: Voxel-wise correlations between gallium-68 ( 68 Ga) positron emission tomography/computed tomography (PET/CT)-measured ventilation and perfusion varied widely among 19 patients with lung cancer (range: 0.26–0.88). 68 Ga PET/CT-measured percent gas exchanging lung volume was moderately correlated with diffusing capacity of the lung for carbon monoxide (DLCO ) as the reference standard, with the highest correlation coefficient of 0.59 ( P < 0.01). 68 Ga PET/CT ventilation/perfusion imaging may provide a reasonable surrogate for regional gas exchange. Abstract: Pulmonary functional imaging has demonstrated potential to improve thoracic radiotherapy. The purpose of this study was twofold: 1) to quantify ventilation/perfusion relationships in lung cancer patients using a new functional imaging approach, gallium-68 ( 68 Ga)-positron emission tomography/computed tomography (PET/CT); and 2) to compare ventilation/perfusion matching with diffusing capacity of the lung for carbon monoxide (DLCO ). Voxel-wise correlations between ventilation and perfusion varied widely among 19 patients (range: 0.26–0.88). 68 Ga-PET/CT-measured percent gas exchanging lung volume was moderately correlated with DLCO (≤0.59). Our findings suggested that 68 Ga-PET/CT ventilation/perfusion imaging provided complementary information and a reasonable surrogate for gas exchange in lung cancer patients.